Peran Barisan Ansor Serbaguna (Banser) dalam Membangun Citra Nahdlatul Ulama sebagai Organisasi Keagamaan - Rizqi Adrika Akbar, Muhammad; Aris Munandar, Moh. (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to analyze the role of Barisan Ansor Serbaguna (Banser) in shaping the image of Nahdlatul Ulama (NU) as a religious organization, using a case study in Gajah District, Demak Regency. The focus of the study is directed toward the identification of the forms of Banser’s roles and how these roles are manifested in social and religious practices. The research method uses a descriptive qualitative approach, with data collection techniques through in-depth interviews with two administrators of Banser Satkoryon PAC Gajah, the head of PAC GP Ansor Gajah, and four residents of Gajah District, as well as through participatory observation and documentation. Data analysis follows the Miles & Huberman model, which involves three stages: data reduction, data display, and conclusion drawing. The findings reveal that Banser has successfully fulfilled its expected role as a protector of NU's religious activities and its actual role through active participation in social initiatives such as traffic regulation, community kitchens, and interfaith event security. The local community generally responds positively to Banser’s presence, viewing it as a courteous, disciplined, and socially concerned representative of NU. However, there is an emerging expectation for Banser to become more engaged in non-religious social activities, which may lead to potential role conflict if not supported by adequate resource development.